MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA MELALUI PENERAPAN METODE PEMBELAJARAN DEMONSTRASI PADA POKOK BAHASAN PERUBAHAN SIFAT BENDA - Ramadhani, Hani Suciati; Sriningsih, Naning; Kelana, Jajang Bayu (COLLASE (Creative of Learning Students Elementary Education), 2018)
The purpose of this study was to examine and recognize the achievement of improving students' creative thinking abilities through the application of demonstration learning methods on the subject of changes in the nature of objects in Ciampel Elementary School. Specifically, the targets to be achieved are as follows: 1) To determine the level of creative thinking of grade V students of SDN Ciampel before the demonstration method is conducted. 2) To determine the level of creative thinking of the fifth grade students of Ciampel Elementary School after the demonstration method was conducted. 3) To find out whether the application of the demonstration method can improve the creative thinking of class V students of SDN Ciampel. The method used is qualitative using classroom action research (CAR). The subject of the research was the fifth grade students with 30 students.